Digital Marketing Communication Model of Banyuwangi Tourism - Yulian Purnama; Syafruddin Rais; Leila Mona Ganiem; Ali Hanafiah (Jurnal Komunikasi Profesional, 2023)
Digital content has become part of the massive public relation movement which makes it worth research in order to gain new insight or new perspective. Banyuwangi Tourism is part of it, making tourism movement through their digital content posted in Instagram of @banyuwangi_tourism. With Qualitative Content analysis, we get to know how it is constructed and discovering that Indonesia is equally contributes to Indonesian tourism even though they’re not dollar owners who trades with dollars. This also proves that tourism still had strong ties with western favoritism.